THE ROLE OF COMPUTER EDUCATIONAL GAMES IN THE INNOVATIVE EDUCATION SYSTEM - Zakirov Sanjar son of Ikromjon (Western European Studies, 2024)
This article examines the use of computer games in the educational process, one of the most powerful socio-psychological factors influencing the spirituality of youth. The results of a social survey and experiments are presented. Suggestions are given on important aspects of creating computer educational games.
Keywords: Ideology; spirituality; information; computer games